The long-run validity of PPP in some major advanced and emerging countries using alternative models - Justice Kyei-Mensah (Cogent Economics & Finance, 2023)
ABSTRACTThe study examines whether the long-run validity of PPP holds in some major advanced and developing economies. The study employed the smooth time-varying cointegration (TVC) and time-varying detrended fluctuation analysis (DFA) methodology, and we are not aware of any study that has applied TVC and DFA to investigate the long-run validity and determinants of the PPP. Using both the US and Japan as base countries, the empirical results from the univariate unit root tests show that PPP does not hold and thus invalidates PPP. The study finds strong evidence for both the VAR model and the TVC. Our results show that PPP can be used for determining equilibrium exchange rates for these 15 countries, under both methods. The results of DFA and the Hurst exponents for real exchange rates (RERs) in absolute values showed that the Hurst exponent is greater than 0.5 in any country, thus persistent and not mean-reverting but in a rolling window form RERs provide mixed results about the validity of PPP in these countries. These results might be different from earlier works due to different techniques applied and also the long period of data used in this study.